Bringing English to Life: The Implementation of the Cambridge Curriculum in SMP Islam Al-Azhar 39 Bukittinggi - Shalihah, Mar; Ramadani, Nesi; Mellian, Yuyud; Arifmiboy (Indonesian Journal Publisher, 2025)
The currently curriculum in Indonesia education is Merdeka curriculum while in one of private school in Bukittinggi used Cambridge curriculum in learning English. This school used Cambridge text book in teaching English at 7 – 9 grade. This research conducted a qualitative research with a case study. The research aims to to find out the implementation of Cambridge curriculum based textbook, the inhibition of the using the textbook and the differences between others English textbook that apply in others curriculum at school in teaching English,. The data collected through depth interview with the English teacher in the school and the data is analyzed use thematic analysis toward the data. The finding of the implementation of the Cambridge Curriculum at SMP Islam Al-Azhar 39 Bukittinggi supports the school's aim to produce confident English speakers by emphasizing listening, speaking, reading and writing skills. However, challenges arise due to differences with the Indonesian curriculum, students' varying levels of proficiency, and the complexity of British English materials. Despite limited resources and a heavy academic workload, the teacher uses innovative methods to motivate students and integrate English into their daily lives.